Tumbasang salawikaing pampolitika Filipino, Sebwano, Ilokano, Bikol, Kapampangan, Pangasinan, Hiligaynon, Waray, Zambal, Mëranaw, Ingles - Boras-Vega, Sheilee; Abad, Sandor B. (Komisyon sa Wikang Filipino, 2021)
Sayings in democracy and politics in the Philippines.